Unlocking mathematical marvels: Exploring number patterns in the Rangku Alu traditional game - Pangestuti, Suci; Prahmana, Rully Charitas Indra; Fran, Frankie A. (Jurnal Elemen, 2024)
Ethnomathematics, an interdisciplinary field at the intersection of cultural studies and mathematics, examines the intricate mathematical practices found within diverse cultural settings. This research focuses on Rangku Alu, a traditional game from Indonesia, to explore its embedded mathematical elements. Using a qualitative ethnographic methodology, the study uncovers the mathematical concepts within the game's cultural context. It traces the origins and cultural importance of Rangku Alu in Manggarai, East Nusa Tenggara, through combining participant observation, interviews, and literature review. The game, which prominently features bamboo, is a staple activity in harvest celebrations and serves as a way to express gratitude. During the game, players engage in synchronized movements that create rhythmic patterns and interactive sequences. The analysis reveals seven distinct numerical patterns, derived from the strikes of bamboo, jumping sequences, and player formations. These patterns include both odd and even sequences, as well as basic arithmetic operations. Rangku Alu not only entertains but also provides a unique setting for exploring numerical concepts. This study highlights the potential of integrating traditional practices like Rangku Alu into mathematics education to promote inclusivity and enhance mathematical understanding in multicultural environments.